Changes of the surface area of Morskie Oko and Wielki Staw in the Tatra Mountains - Choiński, Adam; Zieliński, Artur (Quaestiones Geographicae, 2023)
This dissertation has presented the results of measurements regarding the surface area of Morskie Oko and Wielki Staw lakes performed throughout the period of 140-years with the use of various measurement technologies and analyses of cartographic resources. The research has clearly demonstrated that the obtained results are diverse, which could be influenced by various environmental factors and the time difference of surveys conducted at the ana- lysed objects. Wielki Staw is currently the largest lake in the Polish Tatra Mountains. Its surface area in 2021 covered 33.44 ha. Thus, it appeared to be larger than Morskie Oko, the surface area of which is 1.51 ha. It was also concluded that the difference in the size of these two reservoirs might increase over time since Morskie Oko is situated in an environment that undergoes dynamic transformations and, consequently, has an impact on the evolution of this lake. Moreover, the area surrounding Morskie Oko is one of the most popular tourist locations within the Tatra National Park, which may intensify the anthropogenic impact on the course of, among others, the shoreline.